P209 Disproportionate low albumin and high neutrophil-to-lymphocyte ratio in small bowel adenocarcinoma in long-term Crohn's disease patients. (21st January 2022) - Veisman, I; Oppenheim, A; Sub laban, Z; Kenig, A; Ukashi, O; Shacham-Shmueli, E; Engel, T; Kopylov, U; Ben-Horin, S; Lang, A
Abstract: Background: Although Crohn's disease (CD) is a known risk factor for small bowel adenocarcinoma (SBA), early diagnosis remains a significant clinical challenge with many cases diagnosed inadvertently during small bowel resection or biopsies performed for presumed active or structuring CD. Identification of biomarkers for SBA may lead to early detection and improved prognosis in CD patients. The aim of the study was to explore a possible association between two simple laboratory values – serum albumin levels and neutrophil-to-lymphocyte ratio (NLR) and SBA in CD patients. Methods: A retrospective case-control study comparing long-standing (>10 years) CD patients who have undergone small bowel (SB) resection with carcinoma detection by histopathology examination, compared with long-standing CD patients who underwent SB resection without malignancy detection at a ratio of 1:3 of cases to controls. Demographics, disease behavior, NLR, albumin levels and total parenteral nutrition (TPN) status during the three months period prior to surgery were retrieved and compared between groups. Results: Forty-two patients with long-standing CD were included (11 with SBA and 31 patients without SBA). Median age was 55 [Interquartile range (IQR) 44–65] in the malignancy group and 37 (IQR 31–47) in the no-malignancy group (p-value < 0.05). Median NLR in the three months prior to surgery was 8.5 (IQR 6.2–31.3) in SBA patients and 3.8 (IQR 2.8–5.3) for patients without SBA (p < 0.05). Mean albumin levels during the three months period prior to surgery were significantly lower among patients with SBA compared with patients without SBA (2.6 ± 0.6 g/dL versus 3.5 ± 0.6 g/dL, respectively, p < 0.05), despite SBA patients being treated with TPN for significantly longer duration. Conclusion: CD patients with SBA have statistically significant increased NLR and lower albumin compared with surgically treated CD patients without SBA. If corroborated by further studies, high NLR and disproportionate low albumin levels in long-duration CD patients may be useful biomarkers of SBA.